APPLICATION OF INQUIRY LEARNING MODEL TOWARDS IMPROVING FUTSAL PASSING LEARNING OUTCOMES OF GRADE V STUDENTS OF SDN 2 LINGGARJATI - Dio Muhammad Ridwan; Oman Hadiana (Indonesian Journal of Education Teaching and Learning (IJETL), 2025)
This study examines the effect of inquiry learning model on improving futsal passing learning outcomes of fifth grade students of SDN 2 Linggarjati. Using an experimental method with One Group Pretest-Posttest Design on 30 students as a sample, data was collected through pretest and posttest. The results showed a significant increase in the average futsal passing score from 59.53 to 76.43. The paired sample t-test with a significance of 0.000 (p <0.05) confirmed the significant difference, proving the effectiveness of the inquiry model in improving psychomotor skills. This model encourages active student participation, in line with the theory that emphasizes systematic investigation and independent discovery of knowledge.